A novel nomogram for predicting respiratory adverse events during transport after interventional cardiac catheterization in children - Tong, Chaoyang; Liu, Peiwen; Zhang, Kan; Liu, Ting; Zheng, Jijian (Frontiers in Pediatrics, 2022)
Abstract Objective: The rate and predictors of respiratory adverse events (RAEs) during transport discharged from operating room after interventional cardiac catheterization in children remain unclear. This study aimed to investigate the incidence and predictors, and to construct a nomogram for predicting RAEs during transport in this pediatric surgical treatment. Methods: This prospective cohort study enrolled 290 consecutive pediatric patients who underwent ventricular septal defects (VSD), atrial septal defects (ASD), and patent ductus arteriosus (PDA) between February 2019 and December 2020. Independent predictors were used to develop a nomogram, and a bootstrap resampling approach was used to conduct internal validation. Composite RAEs were defined as the occurrence of at least 1 complication regarding laryngospasm, bronchospasm, apnea, severe cough, airway secretions, airway obstruction, and oxygen desaturation. Results: The rate of RAEs during transport was 23.1% (67 out of 290). Multivariate analysis identified age (vs ≤3yrs, adjusted odds ratio (aOR)=0.507, 95% conﬁdence interval (CI), 0.268-0.958, P=0.036), preoperative upper respiratory tract infections (URI, aOR=2.335, 95% CI, 1.223-4.460, P=0.01), type of surgery (vs VSD, for ASD, aOR= 2.856, 95% CI, 1.272-6.411, P=0.011; for PDA, aOR=5.518, 95% CI, 2.425-12.553, P<0.001), morphine equivalent (vs ≤0.153mg/kg, aOR=2.904, 95% CI,1.371-6.150, P=0.005), atropine usage (aOR=0.463, 95% CI, 0.244-0.879, P=0.019), and RAEs during extubation to transport (aOR=5.004, 95% CI, 2.633-9.511, P<0.001) as independent predictors of RAEs during transport. These six candidate predictors were used to develop a nomogram, which showed a C-statistic value of 0.809 and good calibration (P=0.844). Internal validation revealed similarly good discrimination (C-statistic, 0.782; 95% CI, 0.726-0.837) and calibration. Decision curve analysis (DCA) also demonstrated the clinical usefulness of the nomogram. Conclusions: The high rate of RAEs during transport reminds us of the need for more medical care and attention. The proposed nomogram can reliably identify pediatric patients at high risk of RAEs during transport and guide clinicians to make proper transport plans. Our findings have important and meaningful implications for RAEs risk prediction, clinical intervention and healthcare quality control.